The equation of a circle is (x - h)^2 + (y - k)^2 = r^2
x and y are left alone in a circle equation, while h and k are the coordinates of the center.
Thus, our equation is (x - 7)^2 + (y + 2)^2 = 61
So first you plug 6 into the equation which is 4(6)-10.
Using PEMDAS, you solve what’s in the parenthesis first and you get 24-10.
24-10=14
f(6)=14
Answer:
0.3
Step-by-step explanation:
also its not a sum, its called a product :)
ANSWER
(-3,3)
EXPLANATION
The given function is
Expand
Rewrite in the form:
This implies that,
Complete the square to get,
The function is now in the form:
where (h,k) =(-3,3) is the vertex